Influencing factors of pulmonary dysfunction among community-based population at high-risk for chronic obstructive pulmonary disease in Putuo District， Shanghai - SONG Rongwei; WU Chunxiang; YU Jie; LU Yuqing; ZHANG Fengying (Shanghai yufang yixue, 2025)
ObjectiveTo analyze the influencing factors of pulmonary dysfunction among community-based population at high-risk for chronic obstructive pulmonary disease (COPD), and to establish a risk assessment model to provide a reference basis for accelerating the beforehand prevention and control of COPD and promoting the respiratory health of community-based residents.MethodsIndividuals aged >35 years old, with at least one risk factor except age illustrated in the Guidelines for Primary Diagnosis and Treatment of Chronic Obstructive Lung Disease (2018), and participated in the early screening for COPD from July 2022 to December 2023 were selected as the research subjects, and their lung function was assessed by the forceful expiratory volume in the first second after inhalation of bronchodilator (FEV1)/ forced vital capacity (FVC) <70% and/or the ratio of FEV1 to predicted value (FEV1%Pred) <80% as the diagnostic criteria. In addition, risk factors related to pulmonary dysfunction were analyzed for the establishment of risk assessment model.ResultsA total of 823 individuals aged between 35‒76 years were included, among which 298 (36.21%) were diagnosed with pulmonary dysfunction, 167 (20.29%) with COPD, and 131 (15.92%) with preserved ratio but impaired spirometry. Logistic regression analysis revealed that male gender, increasing age, more frequent smoking, insufficient physical activity, recurrent wheezing, the presence of post-exercise wheezing or coughing, insensitive to airborne allergens, and history of chronic bronchitis or bronchial asthma were correlated with pulmonary dysfunction. The incidence rate of pulmonary dysfunction was 1.99 times higher in males than that in females, 1.81 times more common in those aged between 70‒76 years than those aged <60 years, 2.42 times more common in those who smoked 50‒200 pack-years than in those who smoked 0‒14 pack-years, 1.78 times higher in those who underwent physical activity <600 MET‑min·week-1 than in those who underwent physical activity ≥600 MET‑min·week-1, 2.61 times higher in those suffered recurrent wheezing than in those did not, 1.53 times higher in those with symptoms of post-exercise wheezing or coughing than in those without, 1.61 times higher in those insensitive to airborne allergens than those sensitive, 2.02 times higher in patients with chronic bronchitis than in those without, and 2.41 times higher in patients with bronchial asthma than in those without. The risk assessment model for pulmonary dysfunction constructed on this basis had a total score of 28 points, and the area under the subject operating characteristic (ROC) curve was 0.72, reaching the cut-off point of ROC curve while taking scores ≥10 points as the cut-off value for pulmonary dysfunction.ConclusionIn community-based high-risk COPD population, the incidence rate of pulmonary dysfunction is higher in males than that in females, in addition, which increases with the advancement of age. Smoking,insufficient physical activity,recurrent wheezing,post-exercise wheezing or coughing,insensitive to airborne allergens,and history of chronic bronchitis or bronchial asthma are high risk factors for pulmonary dysfunction. The risk assessment model constructed based on these factors has a good predictive effect in screening high-risk population of COPD, but its effectiveness in screening people at general risk needs to be further validated.